Anthropogenically disturbed potentially toxic elements in roadside topsoils of a suburban region of Bishkek, Central Asia. (11th April 2019) - Ma, Long; Abuduwaili, Jilili; Li, Yaoming; Liu, Wen
Abstract: The ecological environment in Central Asia is vulnerable to pressure from human activity due to the physical geography and climatic fragility of this region. A set of indicators suitable for the future assessment of this pressure needs to be proposed. Thirty‐six topsoil samples (0–5 cm) were collected from roadsides in a suburban region of Bishkek, the capital of the Kyrgyz Republic in Central Asia, and a risk assessment of anthropogenically disturbed potentially toxic elements (PTEs) was systematically conducted with classic statistical methods. The results of detrended correspondence analysis and principal component analysis clearly showed that topsoil samples with high contents of PTEs (Pb, Zn and Cu) were strongly affected by traffic within a distance threshold of 200 m and that anthropogenic effects decreased significantly with increasing distance from the highway. The enrichment factor and anthropogenic contribution for Pb were the highest among the three PTEs, with average values of 2.0% and 47.4%, respectively, suggesting enrichment. However, the results of the human health risk assessment also indicated that noncarcinogenic risks did not occur for any of the anthropogenic PTEs. The reported method provides a new systematic pathway to reveal anthropogenic influences on the geochemical composition of soil. The conclusions of this work will be highly valuable as important guidelines for agriculture, and the results of the PTE contents will provide a scientific basis for soil collection in future studies.